The Effect of Robotic Walking and Activity-based Rehabilitation on Functional Capacity, Secondary Complications & Psychological Well-being in Individuals with Spinal Cord Injury (SCI) - Shackleton, Claire Lauren (Department of Human Biology, 2022)
Activity-based training (ABT) represents the current standard of care in neurological rehabilitation centers around the world. However, innovative rehabilitation techniques have been developed including robotic locomotor training (RLT). The conceptual basis for RLT initially appeared promising; a rehabilitation modality that removes the need for intensive assistance from therapists, whilst facilitating safe and effective over-ground ambulation. However, small sample sizes and a lack of homogeneity across studies have resulted in an underpowered evidence base supporting the efficacy of RLT for SCI rehabilitation. Thus, this randomized control pilot study aimed to investigate the effects of RLT compared to ABT on functional capacity, secondary complications, and psychological well-being in people with SCI after 24-weeks of rehabilitation. Participants with chronic, traumatic motor incomplete SCI were randomized into two intervention groups: RLT (n = 8) and ABT (n = 8) groups. RLT involved solely walking in the Ekso bionic suit. ABT involved a variety of resistance, cardiovascular and flexibility training combined with regular weight-bearing in the standing position. Outcome measures, including functional strength, ambulatory function, pain, spasticity, bladder/bowel, bone density, body composition, quality of life (QoL) and depression were tested at baseline, 6, 12 and 24-weeks of the intervention. There were no significant differences between the intervention groups for lower or upper extremity motor scores (UEMS effect size (ES) = 0.30; LEMS ES = 0.07), back strength (ES = 0.14) and abdominal strength (ES = 0.13) after training. However, both groups showed a significant increase of 2.00 points in UEMS and a significant increase in abdominal strength from pre- to post intervention. Only the RLT group showed a significant change in LEMS, with a mean increase of 3.00 [0.00; 16.5] points over time. Distance walked in the Functional Ambulatory Inventory (SCI-FAI) increased significantly (p = 0.02) over time only for the RLT group. Therefore, the RLT showed promising evidence for potentially inducing functional strength changes and improvements in ambulatory function after 24 weeks of training. There was some evidence to support RLT to induce bowel improvements in individuals with SCI and both interventions appeared to reduce urinary incontinence and improve bladder function (p = 0.04). Total spasticity and pain intensity were similar between groups (p = 0.25; p = 0.96). However, pain interference ratings significantly increased from pre-post intervention for both groups (p = 0.05). RLT prevented the progressive decline of bone mineral density usually occurring in the SCI population, as hip BMD was maintained during RLT; however, it was significantly reduced (p = 0.04) during ABT, with a mean reduction of 0.06 [-0.34, 0.22] g/cm2 (5%) from pre to post intervention. No change in leg fat-free soft tissue mass (FFSTM) occurred between groups or over time (p = 0.32), however, there was a significant 7% increase in arm FFSTM over time for both groups (p < 0.01). The ABT group was more effective (ES = 1.02) in reducing central and peripheral adiposity, with a significant decrease in visceral adipose tissue (VAT) (p = 0.04) and gynoid FM (p = 0.01) over time. Both groups reported increased QoL and decreased depression ratings over time, with the RLT group having a significant change in the general life and physical health domains, p = 0.03, respectively. This pilot trial offers promising evidence for the effectiveness of RLT for improving functional and ambulatory capacity, reducing secondary complications, and potentially improving QoL in people with incomplete SCI. Thus, this dissertation adds substantial weight to the lacking evidence base on the effects of RLT, by incorporating a large homogenous sample, comprehensive testing procedures and an extended intervention period within South Africa.